Evaluation of Pre-Replanting Oil Palm Plant Health using the NDVI Index from Landsat 8 Satellite Imagery - Betti Yuniasih; Alief Rizky Purnama Adji; Budi Budi (The University of Lampung, 2022)
NDVI analysis was calculated based on the ratio of the reflection of red and near infrared waves. Aims of this study is to determine the density condition and health level of oil palm plants that have entered the age of replanting using the NDVI index from Landsat 8 satellite imagery and evaluate the plant health level based on the NDVI index compared with the LSU data. The research was conducted at Afdeling 1 Rantau Baru Plantation, PT. Pusaka Megah Bumi Nusantara, which is a plantation with old oil palm plant that have entered a period of replanting (22-29 years). The NDVI analysis results show the NDVI value is 0.034-0.469. Object identification shows that non-vegetation objects have an NDVI index value of 0.034-0.245 and vegetation objects have a value of 0.273-0.454. The result of the NDVI index shows the density of oil palm plants are categorized in the high category (dense). These results are appropriate with the actual condition of oil palm plantations which have an average density of 118 trees/hectare. The average NDVI value for vegetation objects is 0.423, that indicates the plants are in fairly healthy condition. The level of plant health as the result of the NDVI analysis was in appropriate with the LSU data which showed that the content of macro and micro nutrients in the leaves was quite high. Therefore, NDVI analysis can be an alternative to evaluate the condition of oil palm plantations efficiently. Keywords: Landsat 8 sattelite imagery, NDVI index, Oil palm, Plant density, Plant health